2019
DOI: 10.1007/s12288-019-01144-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum Methotrexate Level and Side Effects of High Dose Methotrexate Infusion in Pediatric Patients with Acute Lymphoblastic Leukaemia (ALL)

Abstract: Methotrexate (MTX) is an extensively prescribed antimetabolite especially in the treatment of several pediatric cancers, though managing toxicities associated with methotrexate in high dose continues to be a challenge. A prospective study was carried out from April 2017 to October 2018. Children of either sex below 18 years at the time of enrolment and receiving high dose Methotrexate intravenous infusion over 24 h as a 2 g/m 2 , 3 g/m 2 and 5 g/ m 2 dose was included in the study. The serum methotrexate level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…However, studies have shown that the risk of relapse may increase when given in high amounts with additional doses (5,10). In contrast, it has been questioned whether long-term folinic acid is harmful or reduces the efficacy of MTX (28). In the present study, folinic acid was administered to the patients at the 42 nd , 48 th , and 54 th hours of MTX infusion, and only those with higher blood MTX levels than expected were given additional doses.…”
Section: O N L I N E F I R S Tmentioning
confidence: 88%
“…However, studies have shown that the risk of relapse may increase when given in high amounts with additional doses (5,10). In contrast, it has been questioned whether long-term folinic acid is harmful or reduces the efficacy of MTX (28). In the present study, folinic acid was administered to the patients at the 42 nd , 48 th , and 54 th hours of MTX infusion, and only those with higher blood MTX levels than expected were given additional doses.…”
Section: O N L I N E F I R S Tmentioning
confidence: 88%
“…To prevent the occurrence of peri-treatment adverse reactions to and complications of MTX, the C MTX at 0 h after the treatment of OS with high-dose MTX should be controlled between 700 and 1000 μmol/L, and the average C MTX levels at 24 h, 48 h, and 72 h should be lower than 10 μmol/L, 1 μmol/L, and 0.1 μmol/L, respectively. C MTX levels exceeding the above ranges indicate delayed MTX excretion, suggesting the occurrence of toxic reactions in the liver, kidney, and heart [ 11 ]. The average C MTX observed at 0 h in this study was 980.05±373.53 μmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…C MTX at 48 h is often used clinically as a predictive time point for the development of hepatotoxicity and nephrotoxicity. However, no in-depth research has been done on whether LP occurs [ 11 ]. This study found that the when the C MTX levels at 6 h and 24 h were greater than 112 μmol/L and 1 μmol/L, respectively, the incidence of LP increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate (MTX) is widely used as a chemotherapy drug for malignant tumors. High-dose methotrexate (HD-MTX) is an effective treatment for extramedullary infiltration and systemic consolidation in children with acute lymphoblastic leukemia (ALL), and it can increase the long-term survival rate in children ( Sajith et al, 2020 ). However, in patients treated with HD-MTX, it may lead to significant toxicity and may even interrupt cancer treatment, resulting in adverse anticancer effects ( Widemann and Adamson, 2006 ).…”
Section: Introductionmentioning
confidence: 99%